Enhancement of Employee Engagement with Ethical AI Enabled 6G Wireless Networks - R, Gowri; Sah, Umesh Prasad; Banerjee, Brinda; Kumar, Maj Vineet (Journal of Mobile Multimedia, 2025)
The potential of the envisioned 6G networks for wireless personal communications to mitigate the challenges of Employee Engagement in organisations is the primacy for this research. Opportunities enabled by 6G architecture for AI/ML in real-time sensor fusion, analysis, and visualisation are explored for integration in Human Resource Information Systems (HRIS). This study attempts to provide insights into the regulatory framework for Ethical AI implementation in Indian landscape with concerns & issues on the proposed Employee Engagement methods. The proposed methods have been validated using qualitative analysis of flash interviews with managers & employees. Findings prove the capability of enhancement of employee engagement methods by providing seamless connectivity, refining employee experiences, and effective workflow management. AI/ML-driven talent management processes can foster career progression and sentiment analysis can provide effective communication. However, the study also identifies future challenges, including system, societal, technological, and ethical concerns. The research concludes by providing policy, technology and ethical approaches to mitigate the impending challenges in 6G environment with specific emphasis on employee engagement strategies.